The impact of age and electrode position on amplitude-integrated EEGs in children from 1 month to 17 years of age - Greve, Sandra; Löffelhardt, Verena Tamara; Della Marina, Adela; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian; Bruns, Nora (Frontiers in Neurology, 2022)
Aim: Amplitude-integrated electroencephalography (aEEG) is used to monitor electrocortical activity in critically ill children but age-specific reference values are lacking. We aimed to assess the impact of age and electrode position on aEEG amplitudes and derive normal values for pediatric aEEGs from neurologically healthy children. Methods: Normal EEGs from awake children aged 1 month to 17 years (213 female, 237 male) without neurological disease or neuroactive medication were retrospectively converted into aEEGs. Two observers manually measured the upper and lower amplitude borders of the C3 – P3, C4 – P4, C3 – C4, P3 – P4, and Fp1 – Fp2 channels of the 10 – 20 system. Percentiles (10th, 25th, 50th, 75th, 90th) were calculated for each age group (< 1 year, 1 year, 2 – 5 years, 6 – 9 years, 10 – 13 years, 14 – 17 years). Results: Amplitude heights and curves differed between channels without sex-specific differences. During the first 2 years of life, upper and lower amplitudes of all but the Fp1 – Fp2 channel increased and then declined until 17 years. The decline of the upper Fp1 – Fp2 amplitude began at four years, while the lower amplitude declined from the first year of life. Conclusions: aEEG interpretation must account for age and electrode positions but not for sex in infants and children.